Effects of supervised moderate aerobic exercise intervention on tobacco withdrawal during temporary smoking abstinence / Nur-Hasanah Ruslan - Ruslan, Nur-Hasanah (2021)
Exercise is an adjunct therapy for smoking cessation to improve tobacco withdrawal symptoms ( (TWS). The TWS occurs following smoking abstinence and is a barrier to quit smoking. This study investigates the effects of exercise intervention on TWS, physiological symptoms, psychological symptoms, and stress-pleasure related hormones, including serum cortisol, serum beta-endorphin, and plasma adrenaline. The selected hormones are potentially involved in regulating TWS. This study was also exploring the experience of an exercise intervention on abstinence-related feelings. This study consists of three phases: validation of the study instrument, an intervention and qualitative study. Validation study involves the validation process for the intervention study instruments, including the Subjective Experience Exercise Scale (SEES), Theory of Planned behaviour (TPB) for smoking cessation and Smoking Cessation Quality of Life (SCQoL). The intervention study was carried out USING a convenience sampling method. Thirty healthy smokers (n=30) were recruited for a moderate aerobic exercise intervention programme three times per week for two months and detraining for two weeks. Then, the 14 smokers (n=14) who underwent the intervention programme were interviewed for the qualitative study based on the Health Belief Model constructs. For the validation study, (n=152) smokers participated in the SEES questionnaire, (n=185) smokers in TPB for smoking cessation and (n=258) for SCQoL. The data underwent exploratory and confirmatory factor analyses. The intervention study measures including psychological, physiological symptoms and stress-pleasure related hormones were analysed using Repeated Measure ANOVA for measuring the impact of exercise at baseline, post-intervention and post-detraining, and correlation at the post-intervention. The result of the qualitative study was analysed using thematic analysis. This study produces a valid and reliable instrument for this study. The intervention study found a significant reduction in TWS (craving component) F (2, 58) =5.26, p<0.01, ƞ2= 0.15, significant reduction of desire to smoke in QSU Brief F (1.39, 40.42) =4.18, p<0.05, ƞ2= 0.12, improved mood using SEES including significant increase in positive well-being F (1.64, 47.6) =4.02, p<0.05, ƞ2= 0.12, reduction of psychological distress F (1.30, 37.75) = 3.93, p<0.05, ƞ2= 0.12, reduced fatigue F (1, 29) =3.70, p<0.05, ƞ2= 0.11, significant increase in peak exploratory rate F (2, 58) = 7.46, p<0.001, ƞ2= 0.21 and significant increase adrenaline F (2, 56) =4.42, p<0.05, ƞ2= 0.14. Unfortunately, this study found a significant reduction in the intention to quit post-exercise intervention F( 1, 29) =3.00, p<0.01, ƞ2= 0.54.The qualitative study found that most participants perceived benefits and self-efficacy toward an exercise intervention on TWS. In conclusion, supervised moderate aerobic exercise intervention significantly improves craving in TWS, psychological symptoms, physiological symptoms and stress-pleasure related hormones. Thus, this type of exercise possibly aids in reducing TWS and their related symptoms during actual smoking cessation, and it is recommended to be considered when designing the future smoking cessation programme.